2006
DOI: 10.1103/physrevlett.96.056101
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Roughening and Pinning of Two Coupled Interfaces in Disordered Media

Abstract: We studied the kinetic roughening dynamic of two coupled interfaces formed in paper wetting experiments at low evaporation rate. We observed three different regimes of impregnation in which kinetic roughening dynamics of coupled precursor and main fronts belong to different universality classes; nevertheless both interfaces are pinned in the same configuration. Reported experimental observations provide a novel insight into the nature of kinetic roughening phenomena occurring in the vast variety of systems far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
2
33
1
2
Order By: Relevance
“…Such experiments, in which the interlayer coupling and the driving field can be rather easily controlled (see, for example, Ref. [30]), have much potential in terms of contributing to the understanding of the dynamics of coupled elastic interfaces in disordered media [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…Such experiments, in which the interlayer coupling and the driving field can be rather easily controlled (see, for example, Ref. [30]), have much potential in terms of contributing to the understanding of the dynamics of coupled elastic interfaces in disordered media [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…Many investigators in their experiments used different samples such as cotton and polyester woven fabric (De Boer 1980), knitted fabrics (Zhuang et al 2002), paper (Eklund and Salminen 1986;Family et al 1992;Horváh and Stanley 1995;Kwon et al 1996;Dubé et al 2000;Balankin et al 2006), Berea (Ma et al 1995;Li et al 2006), glass beads (Delker et al 1996;Li and Horne 2001), Bentonite clay (Brú and Pastor 2006), building materials (Balankin et al 2006). Numerical stimulation studies of porous media (Dubé et al 1999;Lam and Horváth 2000) showed that the LW equation is unsatisfactory when it was applied to the experimental data from capillary imbibition of water, as collected in Table 2.…”
Section: Introductionmentioning
confidence: 97%
“…Balankin et al (2006) thought that this phenomenon of wetting fluid advance in paper could be attributed to the complex time dependent due to swelling structure of paper. Fortunately, the randomness of pore sizes and the heterogeneity of natural porous media have been successfully characterized by fractal geometry such as sandstone rock (Katz and Thompson 1985), soil (Perfect and Kay 1991), artifact porous media (paper (Kopelman et al 1986;Balankin et al 2003), porous glasses (Kopelman et al 1986), porous membranes (Kopelman et al 1986), porous fabrics Shou et al 2010), and nanparticles (Xiao et al 2010a,b)).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Up until now, experimental studies have been restricted to the particular problem of two interfaces moving through a single medium generally while separated by a finite lateral distance [3,16]. In this Letter we consider interface dynamics in a novel type of experimental system consisting instead of two coupled, but physically separate, media.…”
mentioning
confidence: 99%